2021
DOI: 10.3390/ijms222111601
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the miR-363-5p/P2RX4 Axis in Regulating Schwann Cell Phenotype after Nerve Injury

Abstract: Although microRNAs (miRNAs or miRs) have been studied in the peripheral nervous system, their function in Schwann cells remains elusive. In this study, we performed a microRNA array analysis of cyclic adenosine monophosphate (cAMP)-induced differentiated primary Schwann cells. KEGG pathway enrichment analysis of the target genes showed that upregulated miRNAs (mR212-5p, miR335, miR20b-5p, miR146b-3p, and miR363-5p) were related to the calcium signaling pathway, regulation of actin cytoskeleton, retrograde endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Exosomes or micro-RNAs released by Schwann cells can also participate in the modulation of axonal migration (J. Chen et al, 2019;Ching et al, 2018;Sohn et al, 2021). The alteration of one or more of these mechanisms induced by the mutant SOD1 overexpression in Schwann cells may explain their decreased ability to promote MN axonal migration.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes or micro-RNAs released by Schwann cells can also participate in the modulation of axonal migration (J. Chen et al, 2019;Ching et al, 2018;Sohn et al, 2021). The alteration of one or more of these mechanisms induced by the mutant SOD1 overexpression in Schwann cells may explain their decreased ability to promote MN axonal migration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that transcriptional regulation mediated by transcription factors and the post-transcriptional control exerted by miRNAs are often highly coordinated [41][42][43]. In particular, the interplay between miRNAs and transcriptional regulators has been shown to regulate key developmental events or cell-fate decisions [41][42][43]. In particular, one well-described network motif, the double-negative feedback loop, is thought to regulate many binary cell-fate decisions [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the interplay between miRNAs and transcriptional regulators has been shown to regulate key developmental events or cell-fate decisions [41][42][43]. In particular, one well-described network motif, the double-negative feedback loop, is thought to regulate many binary cell-fate decisions [42][43][44]. This regulatory mechanism implies that one miRNA targets a transcriptional regulator, which in turn controls the expression of this miRNA and usually acts as a switch between two alternative cell states [42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a P2X4 receptor antagonist increased the levels of miR-363-5p. In brief, the correlation between miR-363-5p and the P2X4 receptor contributes to the dedifferentiation and migration of Schwann cells after nerve injury [64]. In spinal cord injury (SCI), blockage of P2X7 receptors and other purinergic receptors provides neuroprotection in rats [65][66][67].…”
Section: Purinergic Signalling Modulated By Mirnas In Neurological Diseasesmentioning
confidence: 99%